Stages of proceedings in violation of customs regulations cases - Дуженко, С. А. (Problems of legality, 2014)
This article contains the analyze of scientific points of view regarding the structure of proceedings in administrative cases, particularly about determining the number of its stages. It has been proposed new criterion to determine the stages in proceedings in violation of customs regulations cases, as a kind of proceedings in administrative cases.